Ethanol as a vehicle fuel in China: A review from the perspectives of raw material resource, vehicle, and infrastructure. (10th April 2018) - Jiao, Jianling; Li, Jingjing; Bai, Yu
Abstract: Currently, car ownership in China accounts for 20% of the world's cars, and there is tremendous growth potential in China's motor vehicle market, along with the quick improvement of the urbanization level. These advances will gradually increase the energy and environmental pressures faced by China. A direct and effective method to address these issues is to develop alternative vehicle fuels. This paper elaborates on the necessity and feasibility of developing fuel ethanol in China by comparing fuel ethanol with five kinds of alternative fuels that have either been put into use or are in the demonstration stage. Additionally, we construct a triple-perspective (raw material resource-vehicle-infrastructure) analysis framework. Based on this framework, the review concludes that China should develop 1.5-generation bioethanol in accordance with its own conditions in view of raw material resources. Compared with gasoline, bioethanol has the advantages of having an antiknock ability, engine efficiency and torque output from the perspective of the vehicle, but it also has some performance disadvantages. For infrastructure, the policies regarding using marginal land for planting energy crops lack specific and definite goals. Therefore, the government should increase its investment and develop new varieties of 1.5-generation bioethanol with higher quality and yield; step up efforts to help consumers understand that ethanol is a safer and more friendly antiknock additive than methyl tertiary butyl ethers (MTBE), which should be limited in its additive amount; and assess the environmental and economic feasibility of marginal land used for energy crops. Graphical abstract: Highlights: Bioethanol is reviewed from a triple-perspective framework. China should focus on the development of 1.5-generation bioethanol. Bioethanol should receive more attention as an antiknock and oxygenated additive. The environmental and economic feasibility of marginal land should be assessed.